2012
DOI: 10.1103/physrevlett.109.155303
|View full text |Cite
|
Sign up to set email alerts
|

Strong Isotope Effect in Phase II of Dense Solid Hydrogen and Deuterium

Abstract: Quantum nuclear zero-point motions in solid H2 and D2 under pressure are investigated at 80 K up to 160 GPa by first-principles path-integral molecular dynamics calculations. Molecular orientations are well-defined in phase II of D2, while solid H2 exhibits large and very asymmetric angular quantum fluctuations in this phase, with possible rotation in the (bc) plane, making it difficult to associate a well-identified single classical structure. The mechanism for the transition to phase III is also described. E… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 25 publications
(40 reference statements)
2
35
0
Order By: Relevance
“…For instance, Chen et al (2014) have recently shown in a thorough PIMC benchmark study on H 2 that those cases in which good agreement between standard DFT calculations and experiments is obtained, large error cancellations are likely to be affecting the simulations. Similar conclusions have been attained also by Geneste et al (2012), Morales et al (2013), andDrummond et al (2015) by using non-standard computational approaches (e. g., non-harmonic simulation methods in combination with electronic QMC). In order to provide more conclusive estimations in solid H 2 , therefore, is necessary to employ quantum simulation methods that simultaneously describe QNE (e. g., PIMD, PIMC and PIGS, see Sec.…”
Section: Molecular Crystalssupporting
confidence: 60%
“…For instance, Chen et al (2014) have recently shown in a thorough PIMC benchmark study on H 2 that those cases in which good agreement between standard DFT calculations and experiments is obtained, large error cancellations are likely to be affecting the simulations. Similar conclusions have been attained also by Geneste et al (2012), Morales et al (2013), andDrummond et al (2015) by using non-standard computational approaches (e. g., non-harmonic simulation methods in combination with electronic QMC). In order to provide more conclusive estimations in solid H 2 , therefore, is necessary to employ quantum simulation methods that simultaneously describe QNE (e. g., PIMD, PIMC and PIGS, see Sec.…”
Section: Molecular Crystalssupporting
confidence: 60%
“…A strong isotope effect in phase II of solid H 2 and D 2 was reported by Geneste et al 154 . These authors investigated nuclear quantum motion at 80 K and pressures up to 160 GPa by first-principles PIMD calculations.…”
Section: Molecular Solids a Solid Hydrogenmentioning
confidence: 87%
“…Experimental studies based on static compression revealed three relevant phases of solid molecular hydrogen: phase I (high-temperature, relatively lowpressure phase), phase II (low-temperature, low-pressure phase), and phase III (high-pressure phase). These H 2 phases have been studied in recent years with pathintegral simulations, using effective [147][148][149][150] and ab initio potentials [151][152][153][154][155] . A new phase IV has been recently proposed 156 .…”
Section: Molecular Solids a Solid Hydrogenmentioning
confidence: 99%
“…Furthermore, even though this approach lacks rotational motion, an examination of the rotational energies of a set of candidate structures, including the P 6 3 /m structure, suggests that rotational motion in P ca2 1 is the least energetic (Moraldi, 2009). Although, recent PIMD calculations suggests the possibility that the structure of Phase II is isotope dependent (Geneste et al, 2012), with…”
Section: Fig 4 Possible Molecular Orientations (Indicated Via Arrows)mentioning
confidence: 99%